(untitled) (Research, Society and Development, 2022)
Objective: To validate a scale capable of measuring the construct computer skills for Brazilian nurses. Method: Cross-sectional study, carried out with 550 nurses who developed teaching and care activities. The collection took place through a self-administered Likert-type questionnaire containing 78 computer skills, via Google Forms. Exploratory factor analyzes with Varimax rotation were used. Also, the dimensionality and psychometric analysis of the competencies and the internal consistency of the instrument were verified. Results: The Bartlett tests and the KMO confirmed data correspondence to the factor analysis. Exploratory factor analysis suggested a unidimensional instrument. Four factors were extracted, according to the criteria of the accumulated proportion and the Scree Plot. Four exploratory factor analyzes were applied with Varimax rotation to analyze the factor loadings and commonalities of each item, excluding 12 competencies. The consistency of the instrument was 0.99, verified by Cronbach’s alpha. Conclusion: The scale proved to be valid, with 66 competencies, distributed in four factors, being stable and consistent for its applicability. This management tool will enable the assessment of computer skills and consequent planning of educational strategies in the face of identified weaknesses.